2021
DOI: 10.1186/s12935-021-01784-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of miR-200s in claudin‐low mammary tumor cells alters cell shape and reduces proliferation and invasion potentially through modulating other miRNAs and SUZ12 regulated genes

Abstract: Background MicroRNAs are a class of non-coding RNAs that regulate gene expression through binding to mRNAs and preventing their translation. One family of microRNAs known as the miR-200 family is an important regulator of epithelial identity. The miR-200 family consists of five members expressed in two distinct clusters; the miR-200c/141 cluster and the miR-200b/200a/429 cluster. We have found that murine and human mammary tumor cells with claudin-low characteristics are associated with very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…The miR-200 family has been extensively studied in mammary tumorigenesis, particularly the claudin-low breast cancer subtype by our lab [ 41 , 45 , 46 ] and others [ 47 60 ]. From this research, it has been postulated that miR-200s may serve as therapeutic targets for the treatment or prevention of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The miR-200 family has been extensively studied in mammary tumorigenesis, particularly the claudin-low breast cancer subtype by our lab [ 41 , 45 , 46 ] and others [ 47 60 ]. From this research, it has been postulated that miR-200s may serve as therapeutic targets for the treatment or prevention of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The function of miR-200s in mammary tumor growth and metastasis have been extensively studied using human and murine mammary tumor cell lines. These studies from our lab [23] , [24] , [25] and others [62] , [63] , [64] generally show that miR-200s can inhibit the growth of primary mammary tumors and suppress metastatic spread. However, the ability of miR-200s to prevent mammary tumor initiation, has not been explored.…”
Section: Discussionmentioning
confidence: 78%
“…SUZ12 is a component of the polycomb repressor complex 2 (PRC2) that mono-, di-, and trimethylates histone H3 on lysine 27 (H3K27) leading to chromatin compaction and suppression of transcription [98] , [99] , [100] . Saa1 [77] and Spp1 [101] have been shown to be regulated by H3K27 methylation and our previous study found that increased expression of miR-200s in murine and human breast cancer cells resulted in an elevation of H3K27me3 [24] . Therefore, miR-200s may directly target genes critical for tumor initiation and/or influence histone methylation to regulate gene expression.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations